Sustainability of Durian Agroforestry in the Selat Area, Jambi: Population Structure and Management Challenges in a Changing Landscape - Bambang Hariyadi; Mahya Ihsan; Uni Baroroh Husnudin; Ahmad Sazali (Universitas Labuhanbatu, 2025)
Background: Agroforestry systems integrate agricultural production with environmental conservation, particularly in tropical regions. Although durian-based agroforestry practices have long been established in Jambi, comprehensive studies on their ecological structure, contribution to biodiversity, and sustainability strategies remain limited. This study aims to analyze the population structure of durian trees, agroforestry patterns, biodiversity, as well as the challenges and sustainability strategies of the system. Methodology: Data were collected through vegetation analysis and in-depth interviews conducted in durian agroforestry areas in Selat, Jambi Province. Findings: The results show that agroforestry systems in this region are dominated by old durian trees that have strong associations with other species such as Jengkol (Archidendron pauciflorum), Duku (Lansium domesticum), and Rubber (Hevea brasiliensis). Contribution: This research contributes to biodiversity conservation by providing habitats for local flora and fauna and maintaining ecosystem balance. However, the sustainability of this system faces significant challenges, including land conversion due to population pressure, oil palm plantation expansion, declining durian productivity, and the emergence of the “tasteless durian” phenomenon that reduces fruit quality. Therefore, management strategies focusing on species diversification, tree rejuvenation, and innovations in cultivation technology are essential to sustain durian agroforestry and improve community welfare, particularly in the Selat region